A Persistence Framework for Object-to-Relational and Multidimensional DBMSS - Ming Lim, Tong; Lee, Sai Peck (Malaysian Journal of Computer Science, 2004)
A persistence framework can be defined as a set of Java classes providing functionalities that map objects to a relational database management system (RDBMS) and/or a multidimensional database management system (MDBMS) so that these objects could be saved, retrieved, deleted and queried. Today, many business applications are developed using some kind of object-oriented programming language and objects in these applications are manipulated through SQL statements that are embedded in the application software. When these applications are small and have very little changes, embedding SQL statements in these applications is fine; but for applications which are dynamic and large, such applications are very hard to maintain and manage. Hence, a robust and extendable persistence framework layer that contains classes for mapping objects to a relational DBMS and/or a multidimensional DBMS allows a developer to concentrate on the development of the actual application. The design of the framework uses a set of good object-oriented design patterns that allow developers to extend functionalities and features easily. This allows saving, updating and querying of objects in the persistence store. In short, this paper focuses on the design, development and mapping of objects to the R/MDBMS persistence framework.